الدبلوماسية الاقتصادية كأداة لتنفيذ السياسة الخارجية - سعدون أ. محي الدين صفي (Aljameai, 2023)
المستخلص: يدرس البحث الدبلوماسية الأقتصادية كأداة من أدوات تنفيذ السياسة الخارجية للدولة والمؤسسات والمنظمات الدولية والأقليمية وكنوع من أنواع الدبلوماسية الحديثة والمعاصرة وإبراز مفهومها وتاريخ نشأتها وأهم أدواتها وأساليبها حتى يحقق البحث نتائجه المرجوة بالوصول لفهم موضوعي وسليم للدبلوماسية الاقتصادية. Abstract The research studies economic diplomacy as a tool for implementing the foreign policy of the state, international and regional institutions and organizations, and as a kind of modern and contemporary diplomacy, highlighting its concept, history of its inception, and its most important tools and methods so that the research achieves its desired results by reaching an objective and sound understanding of economic diplomacy